Keefektifan Layanan Bimbingan Kelompok Teknik Sosiodrama Bermuatan Nilai Kakawin Sutasoma untuk Mengelola Kebhinekaan Global Siswa - Fausta, Thadeus Ega; Muslihati, Muslihati; Indreswari, Henny (Bulletin of Counseling and Psychotherapy, 2024)
Global diversity illustrates students' ability to think broadly when encountering cultures different from their own. The aim of this research is to determine whether there is an effect when guidance and counseling services are combined with local Indonesian values, specifically the values contained in Kakawin Sutasoma. The Kakawin Sutasoma is a work by Mpu Tantular, believed to have been written between 1365 and 1389 during the Majapahit kingdom in the 14th century. The Majapahit kingdom had a diverse cultural and religious background, which inspired Mpu Tantular to create a bridge among these various streams to foster unity. This research is a type of quasi-experiment, using a pretest-posttest control group design. The research subjects are 10th-grade students aged 15 to 16 years, selected through purposive sampling, consisting of 8 individuals for the experimental group and 6 individuals for the control group. The control group consists of 4 males and 4 females, while the experimental group has 4 males and 2 females. Data analysis used non-parametric statistical tests employing the Wilcoxon technique, followed by the Mann-Whitney test to compare differences between the experimental and control groups. The results of this study show an Asymp. Sig. (2-tailed) value of 0.008 < 0.05. This means that group guidance with the sociodrama technique incorporating Kakawin Sutasoma values is effective in managing the global diversity attitudes of high school students.